Carbazolic Conjugated Organic Polymers for Visible‐Light‐Driven CO2 Photoreduction with H2O to CO with High Efficiency and Selectivity. Issue 16 (24th June 2022) - Ye, Wenqiang; Wang, Yuepeng; Ji, Guipeng; Zhang, Fengtao; Zhao, Yanfei; Liu, Zhimin
Abstract: Visible‐light‐driven CO2 photoreduction with H2 O to value‐added chemicals in high efficiency and selectivity is significant but challenging. Herein, a series of carbazolic conjugated organic polymers (CB‐COPs) with electron donor–acceptor (D–A) structures were prepared, which showed high efficiency for visible‐light‐driven photocatalytic reduction of CO2 with H2 O in a solid–gas mode, affording CO as the exclusive carbonaceous product. Especially, CB‐COP‐mpd derived from 3, 5‐di(9 H ‐carbazol‐9‐yl)pyridine exhibited the highest CO evolution rate up to 191.46 μmol g −1 h −1 with a selectivity of 100 %. Mechanism studies showed that carbazolyl is a promising electron donor candidate for constructing CB‐COPs with D–A structures, capable of improving the catalytic efficiency and suppressing H2 generation. The acceptor building block with excessive electron withdrawing capability was favorable to H2 O adsorption, thus resulting in the generation of H2 . This work provides new insights for designing COPs photocatalysts for CO2 photocatalytic reduction. Abstract : Give and take : A series of carbazolic conjugated organic polymers (CB‐COPs) with donor–acceptor structures exhibit high performance for visible‐light‐driven CO2 reduction with only H2 O in a solid–gas mode, affording CO as the sole carbonaceous product in 100 % selectivity.